2019
DOI: 10.1021/acs.jmedchem.8b01681
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Bis-styrylbenzo[c]-1,2,5-thiadiazoles as Probes for Fluorescence Microscopy Mapping of Aβ Plaque Heterogeneity

Abstract: A fluorescent bis-styryl-benzothiadiazole (BTD) with carboxylic acid functional groups (X-34/Congo red analogue) showed lower binding affinity toward Aβ1-42 and Aβ1-40 fibrils than its neutral analogue. Hence, variable patterns of neutral OH-substituted bis-styryl-BTDs were generated. All bis-styryl-BTDs showed higher binding affinity to Aβ1-42 fibrils than to Aβ1-40 fibrils. The para-OH on the phenyl rings was beneficial for binding affinity while a meta-OH decreased the affinity. Differential staining of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 52 publications
0
33
0
3
Order By: Relevance
“…14,15 It was also recently shown that several variants of uorescent phenolic styrylbenzo [c]-1,2,5-thiadiazoles, a new uorescent amyloid probe based on benzothiadiazole (BTD) stilbene, can be used for spectral imaging of different amyloid-b (Ab) bril deposits. 16 In this study, we demonstrated that the less toxic and exible insulin laments can be recognized with BTD21, 16 a BTD stilbene ligand. Based on pFTAA and BTD21 staining and hyperspectral microscopy of patient-derived tissue sections of iatrogenic localized insulin amyloidosis (i.e., insulin balls), we demonstrated that a variety of polymorphic amyloid aggregates, such as insulin brils and laments, 6,7 were co-localized in the tissue sections.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…14,15 It was also recently shown that several variants of uorescent phenolic styrylbenzo [c]-1,2,5-thiadiazoles, a new uorescent amyloid probe based on benzothiadiazole (BTD) stilbene, can be used for spectral imaging of different amyloid-b (Ab) bril deposits. 16 In this study, we demonstrated that the less toxic and exible insulin laments can be recognized with BTD21, 16 a BTD stilbene ligand. Based on pFTAA and BTD21 staining and hyperspectral microscopy of patient-derived tissue sections of iatrogenic localized insulin amyloidosis (i.e., insulin balls), we demonstrated that a variety of polymorphic amyloid aggregates, such as insulin brils and laments, 6,7 were co-localized in the tissue sections.…”
Section: Introductionmentioning
confidence: 72%
“…17 More recently, several variants of uorescent BTDs were developed for identifying amyloid polymorphs. 16 The BTD21 compound which lacks the carboxylate groups likely binds in a different binding pocket than Congo red on Ab brils in Alzheimer's disease mouse model brain. 16 Here, we rst examined the binding of pFTAA and BTD21 (chemical structures shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The styrylbenzothiadiazoles previously described and characterized were used to stain A plaques and neurofibrillary tangles or map heterogeneity in A plaques due to spectral shifts or preference towards coronas or core of the plaque [135,136]. Bi-thiophene-vinyl-benzothiazoles (bTVBTs) showed selective detection of tau pathology in brain sections from AD brains [137].…”
Section: Other Ligand Classesmentioning
confidence: 99%